(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Learning burnout is a psychological syndrome that arises from academic tasks and demands beyond a student’s capabilities. It typically manifests as symptoms, including emotional exhaustion from academic tasks, cynicism or apathy, and feelings of inadequacy. Students who experience learning burnout show several symptoms such as laziness, lack of enthusiasm, apathy towards learning, depression, cynicism, indifference, irritability, and pessimism. This PkM aims to educate and assist in practicing Islamic mindfulness in reducing learning burnout. The PkM method consists of situation analysis, PkM implementation, and evaluation by administering pretest and posttest questionnaires, normality testing with the Kolmogorov-Smirnov test, followed by the Wilcoxon test. The results of this PkM obtained an increase in the high category, 23 (37.70%) in the medium category, and 27 (44.26%) in the low category. Meanwhile, the posttest results showed that 23 (37.70%) were in the high category, 30 (49.18%) were in the medium category, and 8 (13.11%) were in the low category. The Wilcoxon Signed Rank Test results, the Z statistic value was obtained at -5.757 with an Asymp. Sig. (2-tailed) value of 0.000. This significance value is less than 0.05 (p < 0.001), so it can be concluded that there is a very significant difference between the scores before and after treatment. This indicates that the Islamic mindfulness education and mentoring intervention significantly increased participants’ knowledge. Conclusion: There was increased knowledge of Islamic mindfulness practices in addressing learning burnout. Based on the results of this PKM activity, it is recommended to use the Islamic mindfulness method to address the problem of learning burnout.